Hart és Holmström szerződéselméleti munkássága - Kóczy Á. László; Kiss Hubert János (Hungarian Academy of Sciences, Institute of Economics, 2017)
– The 2016 Nobel Memorial Prize in Economic Sciences was awarded to Oliver Hart and Bengt Holmström for their work on contract theory. Contract theory is a subfield of game theory where the conflict between the owner - the principal - and the CEO - or agent - is at the centre of interest. In the following we explain the principal-agent model of Holmström with some extensions and then look at the property right aspects of these models based on Hart's work. Although the two researchers are recognised for their theoretical work, in our simple introduction we avoid complex formulae and illustrate the models with examples.
Keywords: C72; D82; D86; 330; contract theory; incentives; principal-agent problem; Nobel prize; risk; property rights